The Rural-Urban Divide: Family Social Capital, Family Cultural Capital, and Educational Outcomes of Chinese Adolescents - Tan, Claire; Fang, Zheng (Journal of Economic Analysis, 2023)
A large body of research has been dedicated to the study of relationships between social or cultural capital and educational outcomes in Western countries. However, few studies have examined these associations in a Chinese context, and even fewer have examined the effects of both forms of capital on educational outcomes simultaneously within a familial context in China. This study offers a reformulation of the associations between family social capital and family cultural capital on the educational outcomes of adolescents in both rural and urban China. Using the structural equation modelling approach and the China Education Panel Survey, this study sheds some new insights – the presence of significant compositional differences in both family social capital and family cultural capital between rural and urban Chinese adolescents, and differential effects of both forms of capital on educational outcomes were found. Family social capital presented larger positive effects on the academic effort and educational aspiration of rural adolescents while having no positive effects in facilitating the academic achievement of both rural and urban adolescents. Meanwhile, family cultural capital presented larger positive effects for urban adolescents on all educational outcomes as compared to their rural counterparts.